Freedom of Speech: Democracy or a Threat to the Country? - Bojezziera Emmet Syaiba Arrasheen Arrasheen; Maula Inayah; Ahmad Dzaki Bagus Andrian; Alya Dwiana Aufani; Dewi Sulistianingsih (Universitas Negeri Semarang, 2026)
Freedom of speech is a fundamental human right protected by Indonesia’s Constitution and is an essential component of democratic life. However, its implementation faces serious challenges due to ambiguous laws, such as the Electronic Information and Transactions Law (ITE Law), and the low level of political and digital literacy among citizens. This study employs a descriptive qualitative method using literature review to examine how freedom of speech is practiced in Indonesia and the factors that hinder it within the Pancasila democratic framework. The findings reveal that freedom of speech remains caught between the protection of individual rights and the pursuit of state stability. Misinterpretations of criticism as threats, coupled with repressive legal actions, have limited public expression. In the digital era, social media provides space for public participation but also raises issues of misinformation and hate speech. Therefore, reforms in regulation, improved digital literacy, and stronger civic education are necessary to align freedom of expression with Pancasila values—ensuring that it is exercised ethically, responsibly, and constructively for the advancement of Indonesian democracy.